2020
DOI: 10.1038/s41467-020-18351-6
|View full text |Cite
|
Sign up to set email alerts
|

Place cell maps slowly develop via competitive learning and conjunctive coding in the dentate gyrus

Abstract: Place cells exhibit spatially selective firing fields that collectively map the continuum of positions in environments; how such activity pattern develops with experience is largely unknown. Here, we record putative granule cells (GCs) and mossy cells (MCs) from the dentate gyrus (DG) over 27 days as mice repetitively run through a sequence of objects fixed onto a treadmill belt. We observe a progressive transformation of GC spatial representations, from a sparse encoding of object locations and spatial patter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 62 publications
(126 reference statements)
9
27
0
Order By: Relevance
“…While most cells maintained a stable, spatial map of the environment, the activity of many DG place cells was affected by the addition or displacement of objects within the environment. Many cells resembled LV cells previously reported in the hippocampus (and similar object-vector cells in entorhinal cortex), 4, 17, 30 with multiple firing fields that shared the same vector relationship to multiple objects. Other cells had place fields that moved when a nearby object was moved, fields that appeared, disappeared, rotated, or moved closer to an object, as well as trace firing at previous object locations.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…While most cells maintained a stable, spatial map of the environment, the activity of many DG place cells was affected by the addition or displacement of objects within the environment. Many cells resembled LV cells previously reported in the hippocampus (and similar object-vector cells in entorhinal cortex), 4, 17, 30 with multiple firing fields that shared the same vector relationship to multiple objects. Other cells had place fields that moved when a nearby object was moved, fields that appeared, disappeared, rotated, or moved closer to an object, as well as trace firing at previous object locations.…”
Section: Discussionsupporting
confidence: 76%
“…Recent studies have reported how tactile cues affect DG activity during learning in head-fixed mice. 30, 31 While mossy cells encoded cue locations throughout learning, cue-associated activity in granule cells was more common early in training. 31 The well-trained task used in the present study may therefore reduce the prevalence of object-related granule cell activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In head-fixed mice, the addition of tactile cues to a treadmill induced or reorganized some granule cell and mossy cell firing fields and revealed differences between the cell types in the timing and duration of cue-modulated firing during learning. [32][33][34] Given the well-established ability of the hippocampus to generate highly stereotyped sequential representations of distance and time in linear tracks and treadmills, it can be difficult to disentangle neural responses to spatial information and tactile cues that are repeatedly experienced by the animal in a particular order. Therefore, it is critical to record from freely moving animals in an environment in which objects can be approached from multiple directions in a 2D coordinate frame to determine how spatial and nonspatial information is represented when not constrained by sequential presentations of stimuli and path-invariant sampling of space.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that DGCs form similar maps in the dentate gyrus after auditory task learning. We performed 5 days of habituation in the decision task apparatus to exclude the neural dynamics from learning the context, however, Kim et al 40 recently showed that the slow emergence of dentate spatial maps plateaus after a week. This could potentially explain the neural activity pattern in “off task” assemblies to RS II or III more than RS I.…”
Section: Discussionmentioning
confidence: 99%